Ultrafast folding of α(3)D: A de novo designed three-helix bundle protein - Zhu, Yongjin (National Academy of Sciences, 2003)
Here, we describe the folding/unfolding kinetics of α(3)D, a small designed three-helix bundle. Both IR temperature jump and ultrafast fluorescence mixing methods reveal a single-exponential process consistent with a minimal folding time of 3.2 ± 1.2 μs (at ≈50°C), indicating that a protein can fold on the 1- to 5-μs time scale. Furthermore, the single-exponential nature of the relaxation indicates that the prefactor for transition state (TS)-folding models is probably ≥1 (μs)(–1) for a protein of this size and topology. Molecular dynamics simulations and IR spectroscopy provide a molecular rationale for the rapid, single-exponential folding of this protein. α(3)D shows a significant bias toward local helical structure in the thermally denatured state. The molecular dynamics-simulated TS ensemble is highly heterogeneous and dynamic, allowing access to the TS via multiple pathways.